STEM-integrated encyclopaedia as the enrichment for elementary school students - Vera Yuli Erviana; Anjar Purba Asmara (Jurnal Prima Edukasia, 2019)
The objective of the study is to describe the effectiveness and the fitness of the STEM-Integrated encyclopaedia as the enrichment for the learning materials of Temperature and Heat among Grade V Students in the elementary school degree. Concerning the objective of the study, the nature of the study is Research and Development (RD). In conducting the RD, the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model had been adopted. In overall, the Analysis was directed toward the problems that had occurred among the students, the Design was related to the media that should be presented to the students, the Development referred to the model of the media that had been in accordance to the needs of the students, the Implemented was related to the Development that had been performed and the Evaluation was directed toward the media that had been developed. In gathering the data, several techniques had been applied namely interview, test administration and questionnaire distribution. Then, in analysing the data both of the qualitative and the quantitative approach had been adopted. Furthermore, in testing the hypothesis, the paired t-test had been administrated to identify the results of the effectiveness of the study. Based on the results of the assessment by the media validator, the material validator and the learning validator, it might be concluded that the STEM-integrated encyclopaedia has been fit for the implementation of the learning process among the Grade V students within the elementary school degree. In the same time, the results of the test show that the effectiveness of the STEM-integrated encyclopaedia has been significant since in the conduct of the hypothesis test (t-test) using the paired t-test it is found that the t-count (10.325) the t-table (2.048). Besides, it is also found that the significance (p-value) has been 0.000, which is lower than the α 5.00% (0.0000 0.050) from the results of the comparison between the pre-test and the post-test. Therefore, the use of the STEM-integrated encyclopaedia has been fit for implementation in the elementary school degree.